2020
DOI: 10.3409/fb_68-1.02
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships within the Poecilimon ornatus Group (Orthoptera: Phaneropterinae) Based on the Cytochrome C Oxidase I Gene

Abstract: The genus Poecilimon includes 142 species divided into 18 groups. It is distributed throughout the Palaearctic area. One of the groups is the Poecilimon ornatus group, in which many closely related taxa have been identified (13 species). Although several searches have been carried out, the phylogeny and systematics of P. ornatus are only partly resolved. The most dispersed taxon within the group is Poecilimon affinis, having numerous subspecies. Species from the P. ornatus group have been described mainly bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 0 publications
5
7
1
Order By: Relevance
“…The BI and ML phylogenetic trees showed the same topology (Fig. 4) and confirmed the monophyly of the P. ornatus group (posterior probability support, PP = 1.0; bootstrap support, BP = 100), whereas the P. affinis complex was paraphyletic as suggested in Kociński (2020). The first clade consists of P. nobilis, P. artedentatus and P. obesus.…”
Section: Resultssupporting
confidence: 66%
See 4 more Smart Citations
“…The BI and ML phylogenetic trees showed the same topology (Fig. 4) and confirmed the monophyly of the P. ornatus group (posterior probability support, PP = 1.0; bootstrap support, BP = 100), whereas the P. affinis complex was paraphyletic as suggested in Kociński (2020). The first clade consists of P. nobilis, P. artedentatus and P. obesus.…”
Section: Resultssupporting
confidence: 66%
“…Recent studies suggested extending this complex with P. hoelzeli Harz, 1966 andP. ornatus (Schmidt, 1850) (Kociński 2020;Kociński et al 2021).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations